1998
DOI: 10.1002/(sici)1096-9098(199803)67:3<168::aid-jso5>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Atypical hyperplasia in the era of stereotactic core needle biopsy

Abstract: Background and Objectives: To characterize both atypical hyperplasia (AH) and the malignancies typically present at open surgical biopsy in women diagnosed with AH by stereotactic core needle biopsy (SCNB). Methods Patients with AH diagnosed by SCNB were advised to undergo surgical biopsy to rule out an associated malignancy. Mammography findings, pathology reports and follow‐up data were analyzed. Results AH was identified by SCNB in 38 of 893 (4.3%) patients. Carcinoma was identified in 12 of 33 (36.4%) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 11 publications
0
14
2
Order By: Relevance
“…4,12,13 Previously, it has been recommended to perform open-breast biopsy in all cases with a high-risk diagnosis on large-core needle biopsy. 14 Some investigators classify large-core needle biopsies containing complex sclerosing lesions (radial scars) as high risk as well, because of their reported 40% risk of being malignant at excision biopsy.…”
Section: Data Handling and Analysismentioning
confidence: 99%
“…4,12,13 Previously, it has been recommended to perform open-breast biopsy in all cases with a high-risk diagnosis on large-core needle biopsy. 14 Some investigators classify large-core needle biopsies containing complex sclerosing lesions (radial scars) as high risk as well, because of their reported 40% risk of being malignant at excision biopsy.…”
Section: Data Handling and Analysismentioning
confidence: 99%
“…The presence of a borderline lesion in open breast biopsies indicates an elevated risk of breast cancer [3][4][5]. Previous studies have shown that finding a borderline lesion in large-core needle biopsies is an indication for open breast biopsy because in 23-50% of the cases the excision biopsy will yield malignancy [2,[6][7][8][9][10]. In cases of ductal carcinoma in situ or invasive breast cancer, surgery is required, including axillary dissection or sentinel node biopsy in cases of invasive breast cancer.…”
Section: (Statistical) Analysismentioning
confidence: 99%
“…Several studies have already demonstrated that when ADH is diagnosed on large-core needle biopsy, the risk of malignancy at surgical biopsy is 33-52% (Liberman et al, 1995;Gadzala et al, 1997;Moore et al, 1997;Fuhrman et al, 1998). Similarly, histological diagnoses of radial scar, lobular carcinoma in situ and atypical lobular hyperplasia on large-core needle biopsy are often associated with invasive or in situ carcinomas (Lee et al, 1997;Liberman et al, 1997;Brown et al, 1998;Fuhrman et al, 1998), and therefore always an indication for surgical biopsy.…”
Section: Meta-analysis Of Diagnostic Accuracymentioning
confidence: 99%